1997
DOI: 10.1093/ndt/12.7.1344
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated renal tubular CD44, hyaluronan, and osteopontin in kdkd mice with interstitial nephritis

Abstract: Prominent CD44 expression by TEC in areas of tubulointerstitial lesions is a characteristic feature of kdkd mice. The de novo appearance of CD44 on injured TEC might allow interaction with the ligands HA and Opn in vivo. Interaction of CD44 with these ligands could participate in the tubulointerstitial inflammatory response in kdkd mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 12 publications
3
71
0
1
Order By: Relevance
“…In autoimmune disease-prone MRL/lpr mice, the level of OPN in serum was found to be increased in association with the onset of autoimmune diseases and expansion of CD3 + /CD4 -/CD8 -T-cells which express OPN mRNA [16]. Several studies have demonstrated the link between OPN overexpression and autoimmune diseases including lupus nephritis [28,29], interstitial nephritis [30], rheumatoid arthritis [31] and pulmonary fibrosis [32]. These findings suggest that there is a quantitative contribution of OPN activity to autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In autoimmune disease-prone MRL/lpr mice, the level of OPN in serum was found to be increased in association with the onset of autoimmune diseases and expansion of CD3 + /CD4 -/CD8 -T-cells which express OPN mRNA [16]. Several studies have demonstrated the link between OPN overexpression and autoimmune diseases including lupus nephritis [28,29], interstitial nephritis [30], rheumatoid arthritis [31] and pulmonary fibrosis [32]. These findings suggest that there is a quantitative contribution of OPN activity to autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting cDNA (0.5 µl) was subjected to PCR with the primers shown in Table I. Eight of the primer sequences were derived from previously published ones, [19][20][21][22] while the others were designed from DDBJ sequences (DNA Database of Japan, Mishima, http://www.ddbj.nig.ac.jp/) with OLIGO Primer Analysis Software (National Biosciences, Plymouth, MN). The templates without reverse transcription were also prepared to evaluate contamination with genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…After being washed three times, various numbers of DCs were cultured together with 1 × 10 5 OT-I CD8 + T cells/well in U-bottomed 96-well plates. Cells were pulsed with 5 μCi/well of [ 3 H]thymidine on day 3 (1 μCi/well for peptide presentation) and then were collected [17][18][19][20][21][22][23][24] h later. T cell proliferation was evaluated by incorporation of [ 3 H]thymidine from triplicate wells.…”
Section: In Vitro Cross-presentation Assaymentioning
confidence: 99%
“…Opn is expressed in activated T cells, DCs and macrophages within 24 h of viral or bacterial infection and may account for resistance to microbial infection 13,16 . Dysregulated expression of Opn, in contrast, has been associated with autoimmune disease in mouse models 14 and in several types of human autoimmune disorders, including lupus nephritis, multiple sclerosis and rheumatoid arthritis [17][18][19][20][21][22] . Although most studies have focused on the activity of secreted Opn as a cytokine or chemokine 14,15,23 , a portion of newly synthesized Opn is retained as intracellular Opn (Opn-i) in the cytoplasm and distinct from secretory vesicles [24][25][26] .…”
mentioning
confidence: 99%